Standard-bearers of equality : America's first abolition movement - Polgar, Paul J.; Omohundro Institute of Early American History & Culture (Williamsburg, Virginia : Omohundro Institute of Early American History and Culture ; Chapel Hill : University of North Carolina Press, 2019)
"Paul Polgar recovers the racially inclusive vision of America's first abolition movement. In showcasing the activities of the Pennsylvania Abolition Society, the New York Manumission Society, and their African American allies during the post-Revolutionary and early national eras, he unearths this coalition's comprehensive agenda for black freedom and equality"--
Introduction: Reimagining American abolitionism -- 1. The making of a movement : progress, problems, and the ambiguous origins of the abolitionist project -- 2. The "just right of freedom" : enforcing and expanding gradual emancipation -- 3. Republicans of color : societal environmentalism and the quest for black citizenship -- 4. "A well grounded hope" : sweeping away the cobwebs of prejudice -- 5. "Unconquerable prejudice" and "alien enemies" : the roots and rise of the American Colonization Society -- 6. A prudent alternative or a dangerous diversion? First movement abolitionists respond to colonization -- Epilogue: A movement forgotten.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on November 20, 2019).
JSTOR
Keywords: Pennsylvania Society for Promoting the Abolition of Slavery -- History; New-York Society for Promoting the Manumission of Slaves, and Protecting Such of Them as Have Been, or May Be Liberated -- History; New-York Society for Promoting the Manumission of Slaves, and Protecting Such of Them as Have Been, or May Be Liberated; Pennsylvania Society for Promoting the Abolition of Slavery; Antislavery movements -- Middle Atlantic States -- History -- 18th century; Antislavery movements -- Middle Atlantic States -- History -- 19th century; Free African Americans -- Political activity; African Americans -- Civil rights -- History; United States -- Race relations -- History; Mouvements antiesclavagistes -- États du Moyen-Atlantique (États-Unis) -- Histoire -- 18e siècle.; Mouvements antiesclavagistes -- États du Moyen-Atlantique (États-Unis) -- Histoire -- 19e siècle.; Noirs américains affranchis -- Activité politique; Noirs américains -- Droits -- Histoire; États-Unis -- Relations raciales -- Histoire; HISTORY -- African American; African Americans -- Civil rights; Antislavery movements; Race relations; Middle Atlantic States; United States; 1700-1899; History